2008
DOI: 10.1007/s10620-008-0536-z
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and Manometric Studies on the Esophagus Following Endoscopic Sclerotherapy

Abstract: It appears that EST causes persistent manometric abnormalities and chronic inflammatory changes in the distal esophagus, the severity of which seems to vary directly with the frequency of sclerotherapy and not amount of sclerosant injected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…[5][6][7] Our results showed a significant percentage of patients with hypotonic LES and a positive correlation between the number of sclerotherapy sessions and LES basal pressure. In fact, Sharma et al 13 showed not only the same results but also noticed that the degree of chronic inflammatory cell infiltrate and fibrosis parallels the number of sessions. There is no previous data on LES relaxation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…[5][6][7] Our results showed a significant percentage of patients with hypotonic LES and a positive correlation between the number of sclerotherapy sessions and LES basal pressure. In fact, Sharma et al 13 showed not only the same results but also noticed that the degree of chronic inflammatory cell infiltrate and fibrosis parallels the number of sessions. There is no previous data on LES relaxation.…”
Section: Discussionmentioning
confidence: 72%
“…Previous reports focused on the alteration of esophageal motility after endoscopic therapy. [3][4][5][6][7][8][9][10][11][12][13] These studies, however, relied on conventional manometry for the evaluation. High-resolution manometry (HRM) is probably a more adequate tool to measure esophageal motility in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although the esophagitis lesions were mild, their frequency and the high index of abnormal 24-h pH-metry readings (about 20 %) confirm the dysmotility secondary to EST. Previous studies on EST [5,22] confirm that EST with PD or EO for esophageal varices causes not only inflammatory changes in the distal esophagus but also dysmotility and GER.…”
Section: Discussionmentioning
confidence: 95%
“…More dilation procedures were required with PD, and EUS evidenced fibrosis in many of such patients. So, the number of procedures more than the amount of sclerosant injected would be related to fibrotic changes [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation